Action Sounds Modulate Arm Reaching Movements - Tajadura-Jiménez, Ana; Marquardt, Torsten; Swapp, David; Kitagawa, Norimichi; Bianchi-Berthouze, Nadia (Frontiers in Psychology, 2016)
Our mental representations of our body are continuously updated through multisensory bodily feedback as we move and interact with our environment. Although it is often assumed that these internal models of body-representation are used to successfully act upon the environment, only a few studies have actually looked at how body-representation changes influence goal-directed actions, and none have looked at this in relation to body-representation changes induced by sound. The present work examines this question for the first time. Participants reached for a target object before and after adaptation periods during which the sounds produced by their hand tapping a surface were spatially manipulated to induce a representation of an elongated arm. After adaptation, participants’ reaching movements were performed in a way consistent with having a longer arm, in that their reaching velocities were reduced. These kinematic changes suggest auditory-driven recalibration of the somatosensory representation of the arm morphology. These results provide support to the hypothesis that one’s represented body size is used as a perceptual ruler to measure objects’ distances and to accordingly guide bodily actions.